2000
DOI: 10.1177/0959353500010003003
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood and Infertility: Viewing Motherhood through the Lens of Infertility

Abstract: This research was motivated by the need to develop positive feminist discourses about women who are infertile and who pursue medical interventions to achieve motherhood. This study analysed how 19 women who wanted children but who could not easily have them constructed their desire for children, motherhood and their infertility. Reasons for wanting children included motherhood as ‘natural instinct’, as ‘a stage in the development of a relationship’ and as ‘social expectation’. These were used to construct moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 9 publications
(10 reference statements)
5
126
0
5
Order By: Relevance
“…Identity motives also refer to gender roles and these motives may be less important for lesbian women than they are for heterosexual men and women. Furthermore, in society, for heterosexual women the identity of being a mother is still evidence of their femininity (Morell, 1994;Ulrich & Weatherall, 2000). It was also found that for social mothers of the fist child who were biological mothers of subsequent children in the lesbian relationship, motives such as parenthood and continuity were more important compared to 'only social mothers.'…”
Section: Discussionmentioning
confidence: 97%
“…Identity motives also refer to gender roles and these motives may be less important for lesbian women than they are for heterosexual men and women. Furthermore, in society, for heterosexual women the identity of being a mother is still evidence of their femininity (Morell, 1994;Ulrich & Weatherall, 2000). It was also found that for social mothers of the fist child who were biological mothers of subsequent children in the lesbian relationship, motives such as parenthood and continuity were more important compared to 'only social mothers.'…”
Section: Discussionmentioning
confidence: 97%
“…The decision to become a mother is shaped by nature, social structure (McMahon, 2004) sociocultural context, and women's personal views of motherhood (Ulrich & Weatherall, 2000). Rewards of childbearing may encompass personal achievement, emotional fulfilment, sense of identity, family continuity, happiness, and life enhancement (Sarantakos, 1996).…”
Section: The Dilemma Of Motherhood or Childlessnessmentioning
confidence: 99%
“…Rewards of childbearing may encompass personal achievement, emotional fulfilment, sense of identity, family continuity, happiness, and life enhancement (Sarantakos, 1996). Motherhood has been reported to offer relationship stability and provide a sense of purpose by, fulfilment, and may offer physical, psychological, and social completeness (Phoenix & Wollett, 1983;Ulrich & Weatherall, 2000). The decision to become a mother is not always socially and emotionally centred on women's lives (Badinter, 1981); however, motherhood is an achieved identity that, for some women,…”
Section: The Dilemma Of Motherhood or Childlessnessmentioning
confidence: 99%
See 2 more Smart Citations